The effect of adhesive thickness on the mechanical behavior of a structural polyurethane adhesive - Banea, Mariana D. (2016)
One parameter that influences the adhesively bonded joints performance is the adhesive layer thickness. Hence, its effect has to be investigated experimentally and should be taken into consideration in the design of adhesive joints. Most of the results from literature are for typical structural epoxy adhesives which are generally formulated to perform in thin sections. However, polyurethane adhesives are designed to perform in thicker sections and might have a different behavior as a function of adhesive thickness. In this study, the effect of adhesive thickness on the mechanical behavior of a structural polyurethane adhesive was investigated. The mode I fracture toughness of the adhesive was measured using double-cantilever beam (DCB) tests with various thicknesses of the adhesive layer ranging from 0.2 to 2 mm. In addition, single lap joints (SLJs) were fabricated and tested to assess the influence of adhesive thickness on the lap-shear strength of the adhesive. An increasing fracture toughness with increasing adhesive thickness was found. The lap-shear strength decreases as the adhesive layer gets thicker, but in contrast to joints with brittle adhesives the decrease trend was less pronounced.